Importance of assisting in football considering the final outcome of the match and league competition system - Basic, D.; Barisic, V.; Dizdar, D. (Acta Kinesiologica, 2016)
Based on 88 matches in 2014/2015 first Croatian football league we established the importance of assisting as a situational efficacy indicator of final outcome of the match and the league competition system. Applying Mann-Whitney test showed that assisting brings a statistically significant difference for the defeated team (p=0,00). Also, observing the correlation (0,84) we can see a high positive relation of assisting to end result in league system of competition. Teams that have a greater number of assisting through a longer time period exhibit a higher degree of technical and tactical quality both in a match and in that time period.